When Fitness Becomes Fatigue: Wearable Technology, Self-Tracking Anxiety, and Health Perception among Gen Z - Eko Perdana Putra; Inaya Nur Aini; Nur Pratiwi (Journal of Public Health Indonesian, 2026)
The rapid adoption of wearable technology has transformed how Generation Z monitors and interprets health through intensive self-tracking practices. Although wearables are widely promoted as tools to enhance fitness and well-being, excessive health monitoring may generate psychological strain and negatively influence health perception. This study aims to examine the effect of wearable usage intensity on health perception among Generation Z and to investigate the mediating role of self-tracking anxiety. A quantitative explanatory survey design was employed. Data were collected from 240 Generation Z respondents who actively use wearable devices and analyzed using Partial Least Squares Structural Equation Modeling. The results indicate that wearable usage intensity has a significant positive effect on self-tracking anxiety. Furthermore, self-tracking anxiety has a significant negative effect on health perception. Mediation analysis confirms that self-tracking anxiety partially mediates the relationship between wearable usage intensity and health perception. These findings reveal a paradox of digital fitness technologies, where increased health monitoring does not necessarily lead to more positive health perceptions. This study contributes to the literature on digital health technology by highlighting the psychological consequences of wearable use and offers practical implications for developing more balanced wearable designs and health technology literacy initiatives.